Pathological evaluations of experimental cottonseed poisoning in mice - Karadaş, Erkan (Scientific and Technical Research Council of Turkey, 1996)
In this study, cottonseed poisoning was induced experimentally in mice. A total of 65 adult mice were used. Mice were divided into five groups one of which served as the control group. Each group, composed of 13 mice, were fed on ground and sifted cottonseed added to the standart ration in the ratio of 0% (Group I, Control group), 10 % (Group II), 15 % (Group III), 20 % (Group IV) and 25% (Group V) for 17 weeks. The most important clinical findings were the reduced growth rate and no birthing in female mice. Total death rate in all groups was calculated as 21%. Macroscopically, primer lesions were serofibrinous exudation in pleural, pericardial and peritoneal cavities along with emaciation and fullness of stomach (alimentary dilatation). Secondarily, severe edema and congestion of the lungs, an accumulation of frothy fluid in the trachea. Myocard degeneration and marked bilateral dilatation of ventricles of the heart, diffuse focal ulcers and erosions on the mucosa of the stomach and intestine along with catarrhal enteritis were noticed. There were congestion of the liver, spleen and kidney. In addition, focal necrosis of the liver was also found. The testes were enlarged by edema and had soft and flabby appearence. In all the organs, microscopic changes connected to macroscopic lesions were also observed. Moreover, manifestations of diffuse hemosiderosis in the liver and the spleen along with severe common testicular degeneration were recorded as the most important microscopic findings of the toxication.
Farelerde deneysel pamuk tohumu toksikasyonu üzerine patolojik araştirmalar
Keywords: Cottonseed; Mice; Morphology